2019
DOI: 10.1111/plb.12994
|View full text |Cite
|
Sign up to set email alerts
|

Elevated [CO2] effects on crops: Advances in understanding acclimation, nitrogen dynamics and interactions with drought and other organisms

Abstract: Future rapid increases in atmospheric CO 2 concentration [CO 2 ] are expected, with values likely to reach~550 ppm by mid-century. This implies that every terrestrial plant will be exposed to nearly 40% more of one of the key resources determining plant growth. In this review we highlight selected areas of plant interactions with elevated [CO 2 ] (e[CO 2 ]), where recently published experiments challenge long-held, simplified views. Focusing on crops, especially in more extreme and variable growing conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 134 publications
(203 reference statements)
9
54
0
1
Order By: Relevance
“…Sorghum only showed greater yields at elevated [CO 2 ] under dry conditions (Ottman et al., 2001). These early experiments provided evidence for the hypothesis that under drought, the benefits of elevated [CO 2 ] would be greater because lower stomatal conductance and canopy evapotranspiration would benefit soil water content, such that crops could sustain growth in a drought cycle for a longer period of time (Kimball, 2016; Leakey et al., 2009; Tausz‐Posch et al., 2019). With more CO 2 x water treatments in recent FACE experiments, Figure 2 shows a different picture for C 3 crops, with an apparently similar average response to elevated [CO 2 ] with and without water deficit.…”
Section: Understanding Interactions: Drought × Elevated [Co2]mentioning
confidence: 99%
“…Sorghum only showed greater yields at elevated [CO 2 ] under dry conditions (Ottman et al., 2001). These early experiments provided evidence for the hypothesis that under drought, the benefits of elevated [CO 2 ] would be greater because lower stomatal conductance and canopy evapotranspiration would benefit soil water content, such that crops could sustain growth in a drought cycle for a longer period of time (Kimball, 2016; Leakey et al., 2009; Tausz‐Posch et al., 2019). With more CO 2 x water treatments in recent FACE experiments, Figure 2 shows a different picture for C 3 crops, with an apparently similar average response to elevated [CO 2 ] with and without water deficit.…”
Section: Understanding Interactions: Drought × Elevated [Co2]mentioning
confidence: 99%
“…We hypothesized there might be a three-way interaction between Hartog Janz SB062 Spitfire SsrT65 Yitpi 1.0 1.1 1.2 1.3 1.4 1.5 SIMPLACE importance of radiation intercepted as illustrated by the models is in sharp contrast with the current literature: among environmental factors hypothesized to influence the response to e[CO 2 ], the scientific focus has rather been on investigating water and nutrient availabilities, sometimes with varying temperatures (see e.g. recent reviews by Kimball, 2016;Tausz-Posch et al, 2020;van der Kooi et al, 2016) while differences in radiation intercepted are not typically among the primary factors being considered. A notable connection, however, is the work by Shimono (2011) and Shimono et al (2014Shimono et al ( , 2019 who suggested using the response to low-density planting (in rice) as a surrogate for grain yield response to e[CO 2 ], although they also argue that the two responses would likely occur through different physiological mechanisms (Shimono et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…However, there are also recent reports that seem to indicate the contrary (Gray et al, 2016) or that there are no consistent differences (van der Kooi, Reich, Löw, De Kok, & Tausz, 2016), leading some to suggest the response to e[CO 2 ] might depend on the timing of the drought experienced by the crop (Bourgault et al, 2017). The relationships between timing and extent of drought and trade-offs between biomass stimulation and leaf level water use efficiency gains have been shown to be especially important in highly variable, semi-arid or Mediterranean field conditions (Tausz-Posch, Tausz, & Bourgault, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic acclimation is related to limited sink strength (Ainsworth et al , 2004; Tausz‐Posch et al , 2020). Sinks are the organs/tissues that consume photosynthates, and their ability to acquire and utilize photosynthates is termed sink strength (Farrer, 1993).…”
Section: Introductionmentioning
confidence: 99%